An Accountability Analysis Of The Implementation Of The Subsidized Housing Assistance Program In Pallangga District, Gowa Regency - Kris Deana Arima Astuti; Herman H; Risma Niswaty; Ismail (International Journal Of Public Policy and Bureaucracy, 2025)
This study aims to identify and describe the implementation of the subsidized housing assistance program in Gowa Regency, particularly in Palangga District. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation. The data were analyzed through data condensation, data display, and conclusion drawing. The findings reveal that the program’s accountability has not been optimal, especially in two key indicators based on Polidano’s (1998) theory: role accountability and retrospective review. The imbalance of power among the Public Works Office (PUPR) as the controller, the Housing and Settlement Office (Perkimtan) as the licensing authority, and the developers as implementers, has led to weak oversight, regulatory non-compliance, and harm to the public. There are 22 housing developments recorded with issues related to permits and building specifications that do not meet standards. This indicates poor stakeholder accountability and declining public trust in the program. Although the government has made efforts to streamline licensing procedures, enhance supervision, impose sanctions on non-compliant developers, and apply stricter selection criteria for aid recipients, these measures remain insufficient. The study recommends strengthening oversight and legal enforcement, developing standardized technical guidelines, conducting more systematic program evaluations, and enhancing inter-agency collaboration and community involvement to promote transparency and accountability in the subsidized housing program.